Injury incidence and severity at the South African Rugby Union (SARU) Youth Weeks Tournaments: a four year study - Marsh, Jarred (Division of Exercise Science and Sports Medicine, 2019)
Introduction Rugby Union (hereinafter referred to as ‘rugby’) is a contact sport with players being exposed to repetitive collisions throughout a match. As the risk of injury is relatively high, incidence surveillance studies within rugby has become popular. However most of the studies have focussed on senior players. The data on injuries among youth rugby players are limited. This makes it difficult to develop the game to make it safer for youth of all ages. Objectives The first objective of this study was to establish if any injury trends exist across different ages of youth rugby players (13 to 18 years). The second objective was to determine the patterns of injuries changed over four years (2011 to 2014). Methods The South African Rugby Union (SA Rugby) hosts four local youth tournaments annually to for local rugby talent: Craven Week under-13, Grant Khomo under-16, Academy Week under-18 and Craven Week under-18. Injury data were collected from the four SARU Youth Week Tournaments between 2011 and 2014. These data were compiled into one central SARU injury surveillance database. Injury categories were used to group data: ‘Type’, ‘Location’, ‘Event’ and ‘Severity’ of injury were assessed. Injuries were defined as either ‘Time-loss’ (those injuries that prevented a player from match participation for one or more days), or ‘Medical attention’ (injuries that required the player to seek medical attention at the time of or after injury but were not required to miss a match). Injury rates were represented by injury incidence densities (IIDs) (corresponding 95% confidence intervals (95% CIs) for IID were calculated for the number of injuries regardless of whether one person was injured more than once) per 1000 hours of match play. Incidence densities were considered to be significantly different from each other if their 95% CIs did not overlap and using Poisson regression analysis. Results The ‘overall’ combined IID across all four years was 54.6 injuries per 1000 hours of match play (95%CI: 51.0-58.2). The combined ‘time-loss’ IID was 18.9 injuries per 1000 hours of match play (95%CI: 16.8-21.0). ‘Time-loss’ injuries were greatest in 2011 (23.2 per 1000 match hours (95% CI: 18.5-28.0)). However, ‘time-loss’ injuries rates were significantly reduced in 2013, when compared to these injury rates in 2011 (13.3 (9.7-17.0). Craven Week under-13 presented significantly greater ‘overall’ injury incidence densities when compared to the older age groups (71.9 per 1000 match hours (95% CI: 62.4-81.4)). Overall, joint/ligament/tendon injuries were most common ‘overall’ and ‘time-loss’ injury sustained by players between 2011 and 2014 (30% and 33% respectively). This was followed closely by concussion injuries, which accounted for 29% of ‘time-loss’ and 12% of ‘overall’ injuries. A large proportion of both ‘overall’ (57%) and ‘time-loss’ (55%) injuries occurred during the tackle event, with the tackler being injured more often than the ball-carrier (37% and 18% respectively). However, there were no statistically significant differences when comparing ‘overall’ and ‘time-loss’ IID between the different tournaments from 2011 until 2014. Discussion Significant differences were found when comparing ‘overall’ and ‘time-loss’ IID between the different tournaments from 2011 until 2014. Craven Week under-13 presented significantly greater ‘overall’ injury incidence densities. This finding contradicts previous literature within youth rugby research. The tackle (combination of tackler and ball-carrier) still accounts for the highest proportion both ‘time-loss’ and ‘overall’ injury events (57% and 55% respectively). This is in accordance with previous studies. However, a point of concern was that concussion accounted for 29% of all ‘time-loss’ injuries and 12% of all ‘overall’ injuries. This finding suggests a gradual increase in the number of concussions suffered during the SARU Youth Week Tournaments between 2011 and 2014. Further research is required to determine the reason for this pattern. Conclusion Further research within youth rugby cohorts is required to determine the risk associated with involvement at various level of participation. Injury prevention programs should place focus on reducing the prevalence of concussion at youth level by educating players and coaches about safe tackle techniques. Future studies should focus on local youth cohorts for seasonal